The Effect of Organizational Flexibility on Organizational Ambidexterity in Higher Education Institutions in Iraq - Zeebaree, Mohammed R. Yaseen (International Review of Management and Marketing, 2024)
The purpose of this research is to examine how different dimensions of organizational flexibility (strategic, structural, and operational) impact organizational ambidexterity within the higher education sector in Iraq. To collect data, a survey instrument is used and a quantitative approach is adopted, with 85 academic staff members participating out of a targeted sample size of 295 lecturers from colleges and institutes within Duhok Polytechnic University (DPU) located in Duhok city, Iraqi Kurdistan Region. Structural Equation Modelling is utilized to determine the direction of the relationship between the variables. Based on the study, it was found that Structure Flexibility has a positive and significant impact on both Exploration and Exploitation of organizational ambidexterity. Additionally, Operational Flexibility also had a significant and positive effect on Exploration and Exploitation. However, the effect of Strategy Flexibility on organizational ambidexterity (Exploration and Exploitation was not significant and surpassed the significance level of 0.05. In addition to the findings, this study addresses the key policy implications, limitations, and recommendations for future research regarding higher education institutions.